A New Proposal for Three-Dimensional Positioning of the Chin Using a Single Computer-Aided Design/Computer-Aided Manufacturing Surgical Guide. Issue 7 (October 2018) - Costa, Pedro Jorge Cavalcante; Demétrio, Maurício Silva; Nogueira, Pedro Thalles Bernardo Carvalho; Rodrigues, Larissa Raposo; Júnior, Paulo Domingos Ribeiro
Abstract : Abstract: The workflow digital to aid the treatment of dentofacial deformities is a reality. Associated with the virtual planning, the creation of surgical guides assists the performance of osteotomies and bone positioning, increasing the accuracy of surgical outcomes. This study aims to present a new method of surgical guide for genioplasty based on the selected osteosynthesis plate.